T is for Trespass : Kinsey Millhone #20 - Grafton, Sue. 1940- (New York : Random House Audio, 2007)
Grafton tackles identity theft and elder abuse in her 20th Kinsey Millhone mystery (after S Is for Silence). Gus Vronsky, Kinsey's elderly next-door neighbor, suffers a fall and needs in-home care. A health-care nurse named Solana Rojas is hired, and Kinsey even does the background check, finding nothing out of order. As Gus's condition deteriorates and Solana limits access to her patient, Kinsey and her landlord, Henry, suspect that something is a little off with Solanaand "little off" doesn't fully describe this identity thief and true sociopath. Digging around more carefully, Kinsey unearths horrifying details of Solana's past and must act quickly to save Gus. This is vintage Grafton, set in the 1980s but scarily current, carefully plotted, and fast paced. Kinsey even flirts with healthful eating (vegetables are consumed), but the reader soon sighs with relief when Kinsey returns to her old habits, frequenting the drive-thru at McDonald's and enjoying pal Rosie's hearty Hungarian fare. Recommended for all public libraries.
"A Marian Wood book."
Keywords: Millhone, Kinsey (Fictitious character) -- Fiction; Women private investigators -- California -- Fiction; Caregivers -- Fiction; Psychopaths -- Fiction; California -- Fiction; Mystery fiction